Serum endothelin concentrations in workers exposed to vibration. Issue 2 (February 1996) - Palmer, K T; Mason, H
Abstract : OBJECTIVES: Endothelin 1 (ET1) is one of a newly discovered family of potent naturally occurring vasoconstrictors produced by the endothelium. A few publications indicated that the peptide may have a role in idiopathic Raynaud's phenomenon and Raynaud's phenomenon secondary to connective tissue disease. The aim of this study was to compare serum endothelin concentrations in people with vibration induced white finger (VWF) with those of controls exposed to vibration, and unexposed (pure) controls. SUBJECTS AND METHODS: Male volunteers from a stonemasonry, two quarries, and an insurance company were classified by questionnaire and clinical examination into men with VWF (cases, n = 31), exposed controls (n = 22), or pure controls (n = 36). All subjects were asked to provide two venous blood specimens: a baseline sample after a period of warm equilibration (30 minutes seated in a warm room and 20 minutes with both hands immersed in a water bath at 37 degrees C); and again after cold challenge (both hands immersed in a water bath at 6 degrees C for six minutes). Serum concentrations of the 21 amino acid peptide endothelin ET1-21 were measured by radioimmunoassay. RESULTS: Baseline concentrations of ET1-21 were found to be lower in cases (mean = 12.2 pmol/l) than in the two control groups (mean = 14.7 pmol/l in exposed controls; mean = 14.3 pmol/l in pure controls). Among cases there was a broad inverse relation between severity, as measured by the Griffin blanching score, and baseline ET1-21 (Spearman rank correlation coefficient -0.58, P < 0.001). Cold challenge provoked an overall rise in ET1-21 in all groups, but larger and significant mean absolute and percentage rises were found in cases (4.1 pmol/l and 54%) than in the control groups (2.6 pmol/l and 21% in exposed controls; 1.5 pmol/l and 20% in pure controls). Similar but more obvious differences occurred when controls were compared with those cases who gave a more severe history of disease (Griffin blanching score > or = 24) and those cases found to blanch after cold challenge. In these case subsets baseline ET1-21 was nearly 50% lower than for controls and a four and a half to fivefold greater percentage rise in ET1-21 occurred upon cold challenge. Differences were significant. Close matching for age and smoking did not alter the principal findings. No significant differences, whether in baseline or cold response, were found between unexposed and exposed controls. CONCLUSIONS: Baseline findings seem to contradict various published series and attempts are made to reconcile the differences. It is suggested that a lower baseline ET1-21 in cases may result from a disease compensation mechanism or damage effect. The large relative rise in serum ET1-21 when cases are cold challenged may contribute directly or indirectly to vasospasm, but a simple mechanism is unlikely and interpretation is limited by the absence of measurements of forearm blood flow.